Intersections between epithelial-mesenchymal plasticity and adenosinergic pathway in cancer - Vedovatto, Samlai (2023)
Epithelial-mesenchymal transition (EMT) represents an essential process associated with the advancement of tumors, resistance to therapy, and unfavorable prognosis in various cancer types. Nevertheless, the endeavor to focus on EMT or partial-EMT has persisted as a formidable challenge. The CD73 enzyme, a crucial ectonucleotidase in the adenosinergic signaling cascade, has been associated with EMT. Additionally, CD73 has been associated with cancer progression and the invasive front of tumors just as ZEB1, a key transcription factor in EMT. The present work provides an overview of the interplay between the adenosinergic pathway and the EMT program, and its implications for the advancement of cancer cells. Firstly, we present an in silico analysis of RNAseq datasets which reveals that numerous tumor types exhibit a noteworthy association between the expression of NT5E (CD73) and an EMT score. Moreover, it is apparent that the collaboration between EMT and the adenosinergic pathway in the advancement of tumors is reliant on the specific cellular context and type of tumor. Emerging evidence indicates a significant association between EMT and the adenosinergic pathway, as so, we centered the next steps of our investigation on examining the associations between ZEB1, a pivotal constituent of EMT, and CD73, a vital element of the adenosinergic pathway. The post-transcriptional regulation of ZEB1 expression was measured in cell lines derived from papillary thyroid carcinoma (PTC) upon silencing of CD73 expression. Cells lacking CD73 exhibited a reduction in the expression of ZEB1. Furthermore, a correlation was observed between the expressions of CD73 and ZEB1 and alterations in cellular morphological features that are implicated in cellular migration, including cell polarity index and cell migration speed. Collectively, our findings suggest that the post-transcriptional control of ZEB1 could be affected by CD73, experiencing suppression in its absence in PTC. Additional research is required to clarify the mechanisms of association between CD73 and ZEB1, with the objective of identifying them as potential therapeutic options for cancer treatment in the foreseeable future.